Synthesis of dispersants to generate fillers for composites designed to have an enhanced echogenic response - Stimpson, Amy (2020)
Ultrasound (US) imaging was identified as an advantageous imaging modality over the typically used X-ray. Thus, composites comprising of dispersed US-visible contrast agents embedded in a thermoplastic polyurethane matrix were made. To form the composite device, a commercially available material was used as a dispersant for microparticles. These coated phosphate-based glass microspheres were used as ultrasound visible contrast agents, in a medical grade polymer matrix. Ultrasound images of hollow tubes were obtained by Children’s National Medical Center (Washington DC, USA), which proved to show promising initial results. Imaging artefacts attributed to poor dispersion were observed, thus optimisation of device focussed on dispersant design. To optimise the dispersion of contrast agent throughout medical devices, bespoke dispersants were designed and synthesised to be more compatible with the matrix polymer. The first technique was to employ a thiol chain transfer agent (CTA) which was a one-pot, high yielding reaction to produce oligomers. The other method was catalytic chain transfer polymerisation (CCTP) followed by post-functionalisation of the vinyl-terminated oligomeric product via thiolene click chemistry. It was found that carboxylic acid containing thiols were excellent CTAs for monomers detailed.